(untitled) (Research, Society and Development, 2022)
The Coronavirus (COVID-19) pandemic hit health services and generated an extra demand for structures, inputs and human resources, which challenged health systems, including maternity hospitals, which did not suspend their activities. Given the specific reality of public maternity hospitals, the study aimed to describe the perception of health teams about the risk work environment of COVID-19. This is a descriptive study with a quantitative approach, carried out with health professionals who worked in the maternal and childcare in public maternity hospitals in the city of Aracaju/SE. The sample was carried out for convenience and included the participation of 218 health professionals who work in these maternity hospitals. The data showed that, in general, the biosafety conditions regarding equipment and training of professionals for its use were not adequate and safe. On the other hand, it is worth noting that professionals and their colleagues did not feel empowered and emotionally safe to face the pandemic. Finally, the study participants reported that the coping strategies were incipient, that the pandemic completely influenced the workload, but did not interfere with the production of work.